TRADISI UANG ADAT PERKAWINAN MASYARAKAT MELAYU PETALANGAN DI DESA AIR TERJUN KECAMATAN BANDAR PETALANGAN KABUPATEN PELALAWAN - Sahfitri, Rita Riati; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted in the Waterfall Village, Bandar Petalangan District, Pelalawan Regency. This study aims to determine the procedures, community views as well as developments and changes that occur in the tradition of giving customary money to Petalangan tribal marriages. This study used a qualitative descriptive method with 5 subjects consisting of 3 key informants and 2 subjects. For data collection in this study using observation, interview and documentation techniques. Petalangan is an indigenous Riau Malay tribe who live in Pelalawan Regency. The Petalangan community has a tradition in marriage, one of which is the tradition of giving customary money. The tradition of giving customary money to the marriage of the Petalangan Malay community is a tradition that has existed from generation to generation from previous ancestors. Customary money is the delivery money that must be paid by the prospective groom to the prospective bride for spending the needs of the wedding party. This tradition has undergone several changes such as; changes to the nominal value of customary money as well as the procedure for determining it. This change in tradition has reaped the pros and cons of several communities and traditional leaders. The Petalangan community considers that customary money is a condition for a wedding party. If there are relatives or neighbors who will carry out the marriage, the first thing to ask is, how much is the customary money. If they feel that the amount of customary money does not match the social status of the prospective bride 's family, then the social sanction is to become a matter of public gossip. Keywords: Petalangan, Customary Money, Social Sanctions, Marriage